2012
DOI: 10.1002/hbm.22142
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral blood flow and gray matter volume covariance patterns of cognition in aging

Abstract: Advancing age results in altered cognitive and neuroimaging-derived markers of neural integrity. Whether cognitive changes are the result of variations in brain measures remains unclear and relating the two across the lifespan poses a unique set of problems. It must be determined whether statistical associations between cognitive and brain measures truly exist and are not epiphenomenal due solely to their shared relationships with age. The purpose of this study was to determine whether cerebral blood flow (CBF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 78 publications
3
44
0
Order By: Relevance
“…Similar patterns of declining structural covariance have been reported in other large-scale distributed brain networks, including executive control networks, which have been implicated in those cognitive functions most susceptible to aging [61]. Indeed, measures of structural covariance, when combined with estimates of cerebral blood flow, explained almost all age-related variance in cognitive performance in a recent report [67]. This last observation speaks to the importance of measuring not simply independent trajectories of regional changes, but covariance patterns describing how volume changes in distributed brain regions cohere across the across the lifespan.…”
Section: Changes In Structural Brain Networksupporting
confidence: 70%
“…Similar patterns of declining structural covariance have been reported in other large-scale distributed brain networks, including executive control networks, which have been implicated in those cognitive functions most susceptible to aging [61]. Indeed, measures of structural covariance, when combined with estimates of cerebral blood flow, explained almost all age-related variance in cognitive performance in a recent report [67]. This last observation speaks to the importance of measuring not simply independent trajectories of regional changes, but covariance patterns describing how volume changes in distributed brain regions cohere across the across the lifespan.…”
Section: Changes In Structural Brain Networksupporting
confidence: 70%
“…Initial analyses revealed particular patterns of correlated atrophy (‘components’) that were subsequently also found in other samples 123,126 — an example of successful experimental replication of brain imaging findings. The functional significance of age-related changes in structural co-variance networks is supported by their links with neuropsychological performance, as the strength of these brain-wide co-variance patterns is correlated with individuals’ scores on memory, attention and cognitive tests 123,127 (even in healthy young subjects 127 ).…”
Section: Structural Co-variance Across the Lifespanmentioning
confidence: 99%
“…Previous research has also shown a link between local cortical atrophy and specific changes in cognitive outcomes (Aguilar et al, 2014; Draganski et al, 2013; Hedden & Gabrieli, 2004; Hedden et al, 2014; Kaup et al, 2011; Raz et al, 1998; Raz & Rodrigue, 2006; Rodrigue & Raz, 2004; Salthouse, 2011). This indicates the need for future studies investigating whether the regional associations between cortical atrophy and arterial stiffness may, in turn, lead to declines in the specific cognitive domains supported by the affected regions (see also Steffener et al, 2013; Zimmerman et al, 2014, for similar approaches).…”
Section: Discussionmentioning
confidence: 99%